Islamic ethics for sustainable development and developing social conscience: an Islamic response to the challenge of ecology today - Pawan Ahmad, Isham (IIUM Press, 2018)
Islamic Ethics for Sustainable Development and Developing Social Conscience: An Islamic Response to the Challenge of Ecology Today Isham Pawan Ahmad* Abstract This paper aims at examining the issue of sustainable development and its ecological implications from religious perspectives. The author focuses on the importance of religious ethics, especially from the perspectives of divine religions such as the Abrahamic faiths, in offering viable solutions to those issues. He narrows the scope of discussion onto Islamic response to the challenges of ecology today and the role of Islamic Ethics in dealing with the issues. The author employs a qualitative methodology that covers critical and textual analyses on materials related to the issues. The research finds that the real problem of sustainable development and ecological issues lies in one of man‘s character traits—greed. Efforts to understand the concept of morality falls under the ambit of Islamic Ethics. Keywords: Sustainability, development, environment, Islam, ethics, religion.